2002
DOI: 10.1002/1615-9861(200209)2:9<1288::aid-prot1288>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of proteome reference maps for cross-species identification of proteins by peptide mass fingerprinting

Abstract: We tested whether proteome reference maps established for one species can be used for cross-species protein identification by comparing two-dimensional protein gel patterns and protein identification data of two closely related bacterial strains and four plant species. First, proteome profiles of two strains of the fully sequenced bacterium Sinorhizobium meliloti were compared as an example of close relatedness, high reproducibility and sequence availability. Secondly, the proteome profiles of three legumes (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…For example, in the case of M. truncatula, which has a partially sequenced genome and a large collection of EST sequences, the positive identification or matching rate using PMF data reached 55% (Watson et al 2003). Even in a few cases, a certain degree of success in identifying putative candidates can be achieved by querying PMF data against other organisms (Mathesius et al 2002). Recently, Kwon and associates (2003) demonstrated that EST databases can be used reliably for high-throughput proteomic studies in an organism without genome information using MS/MS data.…”
Section: Protein Identifications Can Be Achieved With Organisms Withomentioning
confidence: 99%
“…For example, in the case of M. truncatula, which has a partially sequenced genome and a large collection of EST sequences, the positive identification or matching rate using PMF data reached 55% (Watson et al 2003). Even in a few cases, a certain degree of success in identifying putative candidates can be achieved by querying PMF data against other organisms (Mathesius et al 2002). Recently, Kwon and associates (2003) demonstrated that EST databases can be used reliably for high-throughput proteomic studies in an organism without genome information using MS/MS data.…”
Section: Protein Identifications Can Be Achieved With Organisms Withomentioning
confidence: 99%
“…The NADH dehydrogenase subunit 5 (Fragment) of the butterfly, Parnassius ruckbeili ruckbeili (Deckert) (TrEMBL accession number: Q76JY5) has an important number of theoretical peptides with mass values )3000 Da. Concerning the pI and MW, both criteria will be relatively close to theoretical values for species with complete genome sequences in databases, and as far as cross-species identification is concerned, and in order to avoid false positive identification, a molecular mass variation of 630% and a pI variation of 62.0 are generally used [6,45,80,81,91,103,108].…”
Section: Misuse Of Softwaresmentioning
confidence: 93%
“…In any given proteomics study, a key step during the research is the identification of proteins linked to the biological phenomenon under investigation, whatever this may be exactly [5,52,[80][81][82]. This imperative has stimulated the development of many new instruments [83][84][85][86][87][88][89][90] and techniques [90,91], especially protein databases [92] and bioinformatics tools [7,93,94].…”
Section: Protein Identification and Imperative Need Of Softwaresmentioning
confidence: 99%
“…Unfortunately the data can be ambiguous and rely heavily on availability of a proteomic or genomic sequence or at least a substantial EST collection for the species being studied. Cross-species PMF studies from four plant species (Mathesius et al 2002) for instance concluded that PMF data are not particularly useful for inter-species protein identification except for the highly conserved proteins.…”
Section: Fig 6 Maldi-tof Ms Spectrum Of a Thlaspi Protein (Visioli mentioning
confidence: 99%